Answer:
it is a solvable equation
Step-by-step explanation:
(x + 2) -3(x - 4) = 6 and x = 4
if x = 4 then fill in all the x's with 4 so the equation is now:
(4 + 2) -3(4 - 4) = 6
Use PEMDAS
Now the equation is 6 - 3(0) = 6
-3 times 0 is 0 so it's 6-0=6
6 = 6
when you put the 4 in for the x variables and the numbers on both sides of the equal sign are the same it makes the equation true
hope this makes sense and hope it helps :)
Answer:
ok but helppp meeeee nothinggggg
Answer:
2000
Step-by-step explanation:
For a vertical projectile, the equation of motion is expressed h(t)=g+bt+c, where g is gravity, b is the initial upward velocity, and c is the starting height. The maxima of this equation is given by -b/2g, which in this case would be -56/-32, or 1.75 seconds after launch
☺☺☺☺
Answer:
The other person is correct, my bad I got mixed up with the numbers